Perkembangan dan Peranan Radio Berbasis Dakwah Islamiyah - Effendy, Erwan; Rayhan, Aisyah; Harlah, Nur Aisyah; Hasibuan, M. Fauzan (Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
Talking about da'wah and radio, we must distinguish between